Scientific Theology: Shift From Epistemological Transformation To Integrative Axiological Transformation - Eva Dewi; Nelvawita Nelvawita; Sariah Sariah; Rina Rehayati; Suhertina Suhertina; Mochammad Novendri S (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
positivist or materialistic paradigm assumes that if the progress of science and technology can meet human needs, then society becomes independent of religion in its life. This view is, on one hand, accurate when science and technology are only considered in their material aspects. However, when understood in their immaterial aspects, it can raise issues. In Indonesia, the development of science has faced various challenges, including a shift in the nature of scientific research from being proportional (objective analysis) to becoming intentional within bureaucracy and elitism, which can hinder the performance of scientific exploration. Additionally, there is the issue of the sacralization of science, radicalism, the quest for singular truth, and the dichotomy of knowledge. To address the above-mentioned issues, the researcher employs Pierre Felix Bourdieu's Structuralism-Constructivism theory in this study, which acknowledges the role of both subject and object in the development of knowledge. The objective of this research is to explore how the concept of scientific theology shifts from epistemological transformation to integrative axiological transformation as one of the constructive solutions in the development of scholarship in Indonesia. As for the research method, this study utilizes the library research method (literature review) with a qualitative and descriptive analysis approach.The research findings explain that scholarship must be developed with the paradigm of Scientific Theology by transforming normative thinking traditions into applied theoretical thinking traditions, shifting from a tradition of material mastery to methodological mastery, and changing ideological thinking traditions into rational thinking in achieving the integration of religion and science without sacrificing the autonomy of different disciplines in all aspects of life.